Bioinspired Total Syntheses of Secologanin-Related Natural Products: A Demonstration of the Power of Secologanin in the Flask - Sakamoto, Jukiya; Ishikawa, Hayato (Synlett, 2023)
The preparation of natural product libraries by total synthesis has become an extremely important and attractive research topic in organic chemistry. In higher plants, secologanin, which belongs to the monoterpene family, is the starting point for derivation into natural products with different skeletons and biological activities. This Account presents a practical total synthesis of secologanin using an asymmetric organocatalytic cascade reaction. In addition, a collective total synthesis of secologanin-related natural products, such as monoterpenoid indole alkaloids and hetero-oligomeric iridoid glycosides, is described from the synthesized secologanin and its derivatives. To date, we have successfully synthesized 39 secologanin-related natural products using bioinspired strategies with reference to biosynthesis, and in this Account, details of the synthetic strategies for 20 of them are presented. By combining these total syntheses into a single Account, we hope to provide a better view of how the pieces connect to one another and how each piece fits together into the overall body of work.1 Introduction2 A Practical Total Synthesis of Secologanin3 Total Syntheses of 5-Carboxystrictosidine and Related Indole Alkaloid Glycosides4 Total Syntheses of Strictosidine and Related Indole Alkaloid Glycosides5 Total Syntheses of β-Carboline-Type Monoterpenoid Indole Alkaloid Glycosides6 Total Syntheses of Non-Glycosylated Monoterpenoid Indole Alkaloids7 Total Syntheses of Hetero-Oligomeric Iridoid Glycosides8 Conclusion and Future Prospects
Keywords: secologanin; bioinspired transformation; monoterpenoid indole alkaloid; hetero-oligomeric iridoid glycoside; collective total synthesis